Najstarsze ślady osadnictwa słowiańskiego w dorzeczu rzeki Kłodnicy na Górnym Ślasku - Zdaniewicz, Radosław (2023)
The oldest traces of Slavic settlement in the Kłodnica basin certainly date back to the older phases of the early Middle Ages (8th-10th centuries). These include undetermined settlement points, remains of open and naturally defensive settlements, and a stronghold. Early Slavic settlements were concentrated here, similarly to the neighbouring areas, mainly on the flood plain terraces of river valleys, in the case of the Kłodnica river and its smaller and larger tributaries, including the Drama river. Without a doubt, the streams were an important source of drinking water for the population. In addition to life needs, its availability also often played a key role in the economy, and some times, as in the case of larger rivers, even the basis of existence. However, the state of current research on the oldest settlement of Slavs in the Kłodnica basin has never been the subject of a separate scientific work. In recent years, newer geophysical methods have been used to more precisely identify some sites. An analysis was also carried out of previously unpublished materials, discovered during the so-called millennium research, and some artefacts were subjected to specialist expertise. The material collected for analysis is not very extensive, but an attempt to comprehensively summarize the results of older and newer research works and their scientific commentary, in the author’s opinion, will constitute an important starting point for further research on the issue of Slavic settlement in this part of Silesia.
Keywords: Upper Silesia; Slavs; early Middle Ages; slavic settlement; Gliwice